Design of captive portal LAN with redundancy connections - Arie Budiansyah; Dirja Nur Ilham; Rudi Arif Candra (Information Technology and Science (ITScience), 2021)
Captive portal networks are in great demand because users have privileged authentication in the form of usernames and passwords to enter the LAN network without having to share with other users. However, the captive portal network is difficult to implement redundant connection because it must be in the form of a ring topology and the application of a bridge network. Captive portal is a web page for the authentication process to enter the network where the authentication back end can use radius, kerberos, ldap with the AAA framework. Meanwhile, fault tolerance is a redundant connection mechanism as an alternative path provider if the main path is broken. Here there is a tiered mechanism so that fault tolerance can be implemented into the captive portal network. This study describes the process of designing a captive portal network starting from analyzing, conceptualizing and finally designing the network itself. The final result of this research is 2 pieces of redundancy connection network design to the captive portal framework.